Development and Trade Dependence: The Case of Puerto Rico, 1948-1963 - Weisskoff, Richard; Wolff, Edward (The Review of Economics and Statistics, 1975)
The transformation of Puerto Rico from a sugar-monoculture began in the early 1950's and by 1963 created a diversified manufacturing export economy. During these years, gross domestic product more than doubled, while gross investment and exports nearly quadrupled (Table 1). The magnitude of the industrialization, as seen in the rise of the industrial share of GDP by 50% and the decline of the agricultural share by about the same extent, resulted in the doubling of per capita income while employment remained stable.